Setting Up a Modern Macroeconomic Policy Framework in Brazil, 1993-2004 - Werneck, Rogério L. F. (World Bank, Washington, DC, 2017)
This paper keeps an eye on the big picture and follows the long‐lived virtuous circle that, beginning in the mid‐1990s, led to the very successful setting up of a modern macroeconomic policy framework in Brazil, after a decade‐long effort involving four presidential terms. It is an eventful and far from linear history that calls attention to the role of leadership and the complex learning processes that may be involved in the improvement of the quality of economic policy.